2021
DOI: 10.1101/2021.04.16.21255616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Transmission of SARS-CoV-2 in Childcare Facilities: A Longitudinal Study

Abstract: Objectives Previous data indicate that children might play a less crucial role in SARS-CoV-2 transmission than initially assumed. We conducted a study to gain further knowledge on prevalence, transmission and spread of SARS-CoV-2 among preschool children, their parents and caretakers. Study design Children, their parents and care givers in 14 childcare facilities in Dresden, Saxony/ Germany were invited to participate in the KiTaCoviDD19-study between July 2020 and January 2021. Seroprevalence of SARS-CoV-2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…day-care, nurseries or schools) using either longitudinal or cross-sectional designs We only included studies which identified SARS-CoV-2 infection through RT-PCR on oral or nasal samples or through established serological methods. We did not include studies which used less well validated methods such as rapid antigen tests, stool samples [21] or wastewater methods.…”
Section: Eligibilitymentioning
confidence: 99%
“…day-care, nurseries or schools) using either longitudinal or cross-sectional designs We only included studies which identified SARS-CoV-2 infection through RT-PCR on oral or nasal samples or through established serological methods. We did not include studies which used less well validated methods such as rapid antigen tests, stool samples [21] or wastewater methods.…”
Section: Eligibilitymentioning
confidence: 99%
“…We only included studies which identified SARS-CoV-2 infection through RT-PCR on oral or nasal samples or through established serological methods. We did not include studies which used less well validated methods such as rapid antigen tests, stool samples [21] or wastewater methods.…”
Section: Eligibilitymentioning
confidence: 99%